2009
DOI: 10.4315/0362-028x-72.10.2217
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Saffron from the Main Producer Countries

Abstract: A microbiological study of saffron spice was undertaken in the context of a European research project (Methodologies for Implementing International Standards for Saffron Purity and Quality, the acronym for which is SAFFIC), analyzing 79 samples obtained from the main producer countries, namely Greece, Iran, Italy, Morocco, and Spain. Current microbiological quality criteria are the same as for other spices, but saffron is added in minute quantities during the cooking process, so the health risk associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…were detected in 11 studies, whereas four surveys yielded negative results. The latter comprised studies performed in Spain (Cosano et al, 2009), the United States (Johnston et al, 2006), Mexico (García, Iracheta, Galván, & Heredia 2001), or Norway (Johannessen, Loncarevic, & Kruse 2002). Johnston et al, (2006) investigated the microbial quality of fresh produce of domestic and Mexican origin.…”
Section: Salmonella-related Outbreaks Caused By Spices and Herbsmentioning
confidence: 99%
“…were detected in 11 studies, whereas four surveys yielded negative results. The latter comprised studies performed in Spain (Cosano et al, 2009), the United States (Johnston et al, 2006), Mexico (García, Iracheta, Galván, & Heredia 2001), or Norway (Johannessen, Loncarevic, & Kruse 2002). Johnston et al, (2006) investigated the microbial quality of fresh produce of domestic and Mexican origin.…”
Section: Salmonella-related Outbreaks Caused By Spices and Herbsmentioning
confidence: 99%
“…), Bacillus cereus , Clostridium perfringens , Escherichia coli , Salmonella spp., Listeria monocytogenes and Staphylococcus aureus (Cho et al. 2008; Cosano et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found an absence of Salmonella using PCR and culture techniques in 79 samples of saffron from Iran, Greece, Italy, Spain and Morocco (Cosano et al, 2009). To the best of our knowledge, there are no published reports on the isolation of Salmonella in saffron.…”
Section: Introductionmentioning
confidence: 82%